Chemical diversity of accessions of the in vivo germplasm bank of Varronia curassavica (Jacq.) - Queiroz, Tulio Barroso [UNESP] (2020)
Varronia curassavica (Jacq.) is a shrub and perennial plant native to Brazil that has therapeutic, anti-inflammatory and cicatrizing properties. The objective of this work was to study the chemical diversity of the native populations of this species maintained in the in vivo germplasm bank from Montes Claros, Minas Gerais, Brazil. The essential oils of 10 accessions analyzed in triplicate were obtained by hydrodistillation. Fifty-five compounds were detected, 46 of which were identified by GC-MS analysis. Essential oil yield ranged from 0.1 (VC-9) to 1.22% (VC-3) among the studied accessions. Three groups were formed by cluster analysis. Group A presented lower relative abundance of the compounds alpha-humulene (1.4%) and 13-caryophyllene (8.5%). Conversely, in Group B, the most abundant compound was alpha-humulene (31.6%). Group C, with the greatest number of accessions, presented values of up to 6.1 and 41.2% for alpha-humulene and beta-caryophyllene, respectively. Only two accessions (VC-1 and VC-5) presented alpha-humulene content lower than that recommended for phytotherapeutic production. These results, along with consolidating breeding programs, contribute to the conservation of the species.